The Effect of Electromagnetic Coupling Via Planar Spiral Inductor for Wireless Power Transfer - Kang, Chia Chao; Ain, Mohd F (International Journal of Natural Sciences Research, 2014)
Wireless power transfer based on electromagnetic coupling is a popular technique that is used in cases where the connection between wires are troublesome or inconvenient. Recently, it has drawn a lot of attention due to increased usage of mobile devices which needed wireless charging. In this paper, a method using circular planar spiral inductor structure to wirelessly transfer energy is proposed. It represents the characteristic of two parallel air core inductor mutually coupled in the free space for wireless power transfer system. Coupled inductance theory is used to compute the resonant frequency and power transfer efficiency. Simulations show that the change of air gap distance is found to be affecting the power transfer efficiency and is described in this paper.